2023
DOI: 10.3390/ijms24087271
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Induced by Ammonium/Nitrate Ratio Ameliorates Low-Light Stress in Brassica pekinesis: Regulation of Photosynthesis and Root Architecture

Abstract: Low-light intensity affects plant growth and development and, finally, causes a decrease in yield and quality. There is a need for improved cropping strategies to solve the problem. We previously demonstrated that moderate ammonium:nitrate ratio (NH4+:NO3−) mitigated the adverse effect caused by low-light stress, although the mechanism behind this alleviation is unclear. The hypothesis that the synthesis of nitric oxide (NO) induced by moderate NH4+:NO3− (10:90) involved in regulating photosynthesis and root a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…To explore if external GSH influenced the photosynthetic capacity of tomato seedlings under salt stress through modulating endogenous NO levels, we treated tomato seedlings under salt stress with exogenous Hb, a NO scavenger. Numerous studies have previously demonstrated the ability of external Hb to efficiently decrease endogenous NO levels in plants ( Shao et al., 2010 ; Lee and Hwang, 2015 ; Bahmani et al., 2019 ; Hu et al., 2023 ). In this investigation, the application of Hb not only resulted in a further reduction in P n and endogenous NO levels under salt stress but also attenuated the beneficial impacts of GSH treatment, including the rise in P n and endogenous NO levels.…”
Section: Discussionmentioning
confidence: 99%
“…To explore if external GSH influenced the photosynthetic capacity of tomato seedlings under salt stress through modulating endogenous NO levels, we treated tomato seedlings under salt stress with exogenous Hb, a NO scavenger. Numerous studies have previously demonstrated the ability of external Hb to efficiently decrease endogenous NO levels in plants ( Shao et al., 2010 ; Lee and Hwang, 2015 ; Bahmani et al., 2019 ; Hu et al., 2023 ). In this investigation, the application of Hb not only resulted in a further reduction in P n and endogenous NO levels under salt stress but also attenuated the beneficial impacts of GSH treatment, including the rise in P n and endogenous NO levels.…”
Section: Discussionmentioning
confidence: 99%
“…Plant roots possess a multitude of basic self-adaptive capabilities, encompassing water and nutrient absorption, soil anchorage, and the establishment of symbiotic relationships with root-associated biological communities. Consequently, the diverse forms of nitrogen can exert significant impacts on plant root structures [ 29 , 30 ]. In this study, we observed that in comparison to the sole application of a single nitrogen source, utilizing a blend of 25%NN:75%UN (T12) or 75%NN:25%AN (T4) significantly enhanced the primary root length, root surface area, root volume, and the number of root tips in tomato plants, thereby promoting the development of an extensive root system.…”
Section: Discussionmentioning
confidence: 99%